2018
DOI: 10.1002/anie.201800816
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐Ion Endohedral Fullerene (Li+@C60) Dopants in Stable Perovskite Solar Cells Induce Instant Doping and Anti‐Oxidation

Abstract: Herein, we report use of [Li @C ]TFSI as a dopant for spiro-MeOTAD in lead halide perovskite solar cells. This approach gave an air stability nearly 10-fold that of conventional devices using Li TFSI . Such high stability is attributed to the hydrophobic nature of [Li @C ]TFSI repelling moisture and absorbing intruding oxygen, thereby protecting the perovskite device from degradation. Furthermore, [Li @C ]TFSI could oxidize spiro-MeOTAD without the need for oxygen. The encapsulated devices exhibited outstandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 54 publications
0
73
0
Order By: Relevance
“…It has further been shown that these surface states can be passivated by insertion of a complementary weak Lewis base [32] such as the CH 3 NH 3 + cation used in these materials which would be expected to lower O 2 or humidity susceptibility by limiting O 2 or H 2 O ingress to the vulnerable perovskite phase. Related approaches to improve stability have included the use of [Li+@C60] bis(trifluoromethanesulfonyl)imide (TFSI -)-doped N2,N2,N2 ,N2 ,N7,N7,N7 ,N7 -octakis(4-methoxyphenyl)-9,9 -spirobi[9H-fluorene]-2,2 ,7,7 -tetramine (spiro-OMeTAD) [33] or spiro-OMeTAD-infiltrated carbon nanotubes [34] as the hole transporting layer to increase hydrophobicity. It is also known that transitional aluminas (for example, γ-Al 2 O 3 ) have an appreciable Lewis acidity, and that coordinatively unsaturated aluminium ions play a role of Lewis acid sites on the alumina surface [35].…”
Section: Device Stability Discussionmentioning
confidence: 99%
“…It has further been shown that these surface states can be passivated by insertion of a complementary weak Lewis base [32] such as the CH 3 NH 3 + cation used in these materials which would be expected to lower O 2 or humidity susceptibility by limiting O 2 or H 2 O ingress to the vulnerable perovskite phase. Related approaches to improve stability have included the use of [Li+@C60] bis(trifluoromethanesulfonyl)imide (TFSI -)-doped N2,N2,N2 ,N2 ,N7,N7,N7 ,N7 -octakis(4-methoxyphenyl)-9,9 -spirobi[9H-fluorene]-2,2 ,7,7 -tetramine (spiro-OMeTAD) [33] or spiro-OMeTAD-infiltrated carbon nanotubes [34] as the hole transporting layer to increase hydrophobicity. It is also known that transitional aluminas (for example, γ-Al 2 O 3 ) have an appreciable Lewis acidity, and that coordinatively unsaturated aluminium ions play a role of Lewis acid sites on the alumina surface [35].…”
Section: Device Stability Discussionmentioning
confidence: 99%
“…The device using 5 also showed excellent stability. The spiro-OMeTAD systems require hygroscopic dopants, 47 which results PCE decreasing by 45% aer 30 days in the atmosphere (20-25 C, 40-45%), whereas the devices using 5 showed a decrease of only 15%. Azmi et al synthesized three types of zinc porphyrins bearing triphenylamino groups (7)(8)(9) to investigate the effect of introducing uorine, an electrophilic group, on the porphyrin substituents with the aim of improving electrochemical properties and device performance.…”
Section: Porphyrins As Hole-transport Materials In Perovskite Solar Cmentioning
confidence: 99%
“…[60][61][62][63] C 60 and its derivatives have readily been used as organic electron acceptors in organic photoactive layers and as electron-transporting layers in perovskite solar cells. [64][65][66][67][68] With the emergence of flexible and stretchable electronics, the number of reports on SWNT-based solar cells has increased dramatically in recent years. 1,4 In one of the examples, SWNT films were used as both an anode and cathode, and the cathode SWNT film was soaked in phenyl-C 61butyric acid methyl ester (PC 61 BM).…”
Section: Introductionmentioning
confidence: 99%